Improving High School Students' Short Story Reading Outcomes With CIRC Model Assisted Image Media - Asep Muhyidin; Farid Ibnu Wahid; Sobri Sobri; Darnita Diana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The low learning outcomes of students’ reading comprehension of SMAN 4 Serang City are influenced by many factors, including the use of learning models and learning media. This study aims to determine the increase in students' ability to read short stories through the CIRC model assisted by media images. This research is a classroom action research using two cycles. Following the Kemmis and McTaggart model, this  model is based on a spiral cycle consisting of four components, namely: planning, implementation, observation, and reflection. The research subject were 42 of class XI IPA-2 at SMAN 4 Serang City in the even semester of the 2021/2022 academic year. Determination of the research sample using purposive sampling methods with a random technique. Data on students’ reading ability were collected using a  reading comprehension test. Data were analyzed descriptively qualitatively. The result showed that the learning model applied has been empirically proven to improve student learning outcomes by reading student stories. From tests that has been carried out for two cycles, it was found that there is a very significant difference between the pretest results and the posttest results. The average value of the final test results, namely after learning using the Cooperative Integrated Reading And Composition (CIRC) learning model and the image media developed, has increased significantly compared to the average value of the initial test results, namely before the developed learning model. So it can be concluded that learning using the Cooperative Integrated Reading And Composition (CIRC) type learning model and serial image media has been proven through a series of tests to improve student learning outcomes for grade XI students of SMAN 4 Serang City.